Quasi-Periodic Oscillatory Motion of Particles Orbiting a Distorted, Deformed Compact Object - Shokoufe Faraji (MDPI AG, 2021)
This work explores the dynamic properties of test particles surrounding a distorted, deformed compact object. The astrophysical motivation was to choose such a background as to constitute a more reasonable model of a real situation that arises in the vicinity of compact objects with the possibility of having parameters such as the extra physical degrees of freedom. This can facilitate associating observational data with astrophysical systems. This work’s main goal is to study the dynamic regime of motion and quasi-periodic oscillation in this background, depending on different parameters of the system. In addition, we exercise the resonant phenomena of the radial and vertical oscillations at their observed quasi-periodic oscillations frequency ratio 3:2 and show that the oscillatory frequencies of charged particles can be adequately related to the frequencies of the twin high-frequency quasi-periodic oscillations observed in some sources of the microquasar observational data.